Novel hydroxyl carboximates derived from β-elemene: design, synthesis and anti-tumour activities evaluation - Yuan Gao; Nian-Dong Mao; Hao Che; Li Xu; Renren Bai; Li-Wei Wang; Xiang-Yang Ye; Tian Xie (Taylor & Francis Group, 2022)
A series of novel N-alkyl-N-hydroxyl carboximates derived from β-elemene were fortuitously discovered. Most of them showed more potent anti-proliferative activities than their lead compound β-elemene (1). Notably, compound 11i exhibited significant inhibitory effects on the proliferation of three lung cell lines (H1975, A549 and H460) and several other tumour cell lines (H1299, U87MG, MV4-11, and SU-DHL-2). Preliminary mechanistic studies revealed that compound 11i could significantly induce cell apoptosis. Further in vivo study in the H460 xenograft mouse model validated the anti-tumour activities of 11i with a greater tumour growth inhibition (TGI, 68.3%) than β-elemene and SAHA (50.1% and 55.9% respectively) at 60 mg/kg ip dosing, without obvious body weight loss and toxicity. Thus, such N-alkyl-N-hydroxyl carboximate class of compounds exemplified as 11i demonstrated potent anticancer activities both in vitro and in vivo, and should warrant further investigation for potential anticancer therapy.